Standing photonic jets for stable nanoparticle trapping in cut-cylinder microfluidic channels; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 350 - Li Renxian; Yuexiao Jiao; Li Xiao; Tang Huan; Wei Bing; Gong Shuhong; Novitsky D. Denis; Minin I. V. Igor Vladilenovich; Minin O. V. Oleg Vladilenovich (2026, 2026)
Optical forces proved to be extremely useful for manipulating and trapping nano- and microparticles. Such applications are especially needed for microfluidic systems to reliably control streams of nanoparticles. In this paper, we propose to optically trap nanoparticles using an inclined photonic jet modulated by a standing wave and generated with a cut cylinder partially blocked from the incident plane waves by a variable metal screen. Our theoretical analysis is based on the Finite Difference Frequency Domain (FDFD) method for the electric field and the optical energy flux calculations and on the Rayleigh model for the optical force calculation. The effects of the cut-cylinder central angle and shape of the metal screen on the standing wave formation and the optical force distribution are numerically demonstrated. We show that the quality of the optical trap can be increased by adjusting the parameters of the model cut-cylinder central angle and estimating the stability of the resulting trap. The cut cylinder can be used as an ingenious microfluidic channel that has potential applications for the optical trapping of nanoparticles and the development of optical tweezers